Recent changes in spatiotemporal patterns of heat extremes in South Asia - Abhirup Banerjee; Shraddha Gupta; Pranava Priyanshu; Ankan Kar; Ruby Saha; Tanujit Chakraborty; Dibakar Ghosh; Jürgen Kurths; Chittaranjan Hens (npj Climate and Atmospheric Science)
Abstract The likelihood of intense heatwaves in South Asia is increasing due to climate change, highlighting the need to understand their evolving spatiotemporal patterns. Using a complex network-based approach, we analyze synchronous extreme heat events across South and West Asia over three 30-year periods: two historical phases (1960–1989, 1990–2019) and a near-future projection (2020–2049) under the SSP2-4.5 scenario. Our findings reveal a shift in heatwave synchronization from western and central Asia before 1990 towards Pakistan, northwest India, and the southwestern Tibetan Plateau by the mid-21st century. This shift is primarily driven by increased surface sensible heat flux, which enhances atmospheric diabatic heating and strengthens the early-summer circumglobal teleconnection. Additionally, atmospheric conditions over the North Atlantic-Greenland sector modulate South Asian heatwave synchronization. Our study provides novel insights into the evolving land-atmosphere interactions driving extreme heat events, with implications for heatwave predictability and risk assessment in a warming world.